Third Cranial Nerve Palsy Presenting with Unilateral Diplopia and Strabismus in a 24-Year-Old Woman with COVID-19 - Belghmaidi, Sarah (Am J Case Rep, 2020)
Patient: Female, 24-year-old Final Diagnosis: Third cranial nerve palsy in a women presenting COVID-19 Symptoms: Ophthalmoplegia Medication:— Clinical Procedure: — Specialty: Ophthalmology OBJECTIVE: Rare disease BACKGROUND: Coronavirus disease (COVID 19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and is the causative agent of a serious disease that is of great global public health concern. Palsy of the third cranial nerve is very rare in patients with confirmed 2019 novel coronavirus disease (COVID-19). We describe the case of a patient with an incomplete palsy of the left third cranial nerve sparing the pupils in the context of SARS-CoV-2 virus infection. CASE REPORT: We report the case of a 24-year-old woman with confirmed COVID-19, which presented with acute onset of diplopia and strabismus of the left eye that occurred 3 days after the start of general symptoms. The patient had no significant medical history. Based on detailed ophthalmic and neurological examination, acute painless incomplete palsy of the third cranial nerve was suspected. Oculo-cerebral magnetic resonance angiography was unremarkable. Blood tests revealed mild normocytic regenerative anemia. According to the Moroccan recommendations, chloroquine and azithromycin were started. After what, a quick improvement of exotropia and diplopia was observed, and complete recovery was obtained by the sixth day of treatment. No adverse effects of the treatment were noted. CONCLUSIONS: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can cause neurological complications such as cranial nerve palsy. The pathological mechanism remains unclear. Full recovery of the ocular motricity is possible, and prognosis depends on the severity of the respiratory illness.